2018
DOI: 10.1016/j.cmet.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic Stimulation Is Not a Requirement for M2 Macrophage Differentiation

Abstract: Enhanced glucose uptake and a switch to glycolysis are key traits of M1 macrophages, whereas enhanced fatty acid oxidation and oxidative phosphorylation are the main metabolic characteristics of M2 macrophages. Recent studies challenge this traditional view, indicating that glycolysis may also be critically important for M2 macrophage differentiation, based on experiments with 2-DG. Here we confirm the inhibitory effect of 2-DG on glycolysis, but also demonstrate that 2-DG impairs oxidative phosphorylation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
249
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(267 citation statements)
references
References 45 publications
(85 reference statements)
13
249
1
4
Order By: Relevance
“…IL‐10 drives the metabolic shift from glycolysis to oxidative phosphorylation (OXPHOS) in macrophages. This glycolytic shift is crucial in shaping the phenotypes of macrophages as OXPHOS is important for M2 macrophage differentiation . Therefore, IL‐10 is critical in controlling the overall redox status and polarization of macrophages through regulating autophagy.…”
Section: Obesity Reinforces Machinery Of Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐10 drives the metabolic shift from glycolysis to oxidative phosphorylation (OXPHOS) in macrophages. This glycolytic shift is crucial in shaping the phenotypes of macrophages as OXPHOS is important for M2 macrophage differentiation . Therefore, IL‐10 is critical in controlling the overall redox status and polarization of macrophages through regulating autophagy.…”
Section: Obesity Reinforces Machinery Of Ageingmentioning
confidence: 99%
“…This glycolytic shift is crucial in shaping the phenotypes of macrophages as OXPHOS is important for M2 macrophage differentiation. 67 Therefore, IL-10 is critical in controlling the overall redox status and polarization of macrophages through regulating autophagy. It is worth noting that low levels of IL-10 has been associated with metabolic syndrome 68 , dyslipidaemia, 69 and android obesity.…”
Section: Insufficient Autophagy and Apoptosismentioning
confidence: 99%
“…Macrophages are typically divided into classically activated M1 subtype and alternatively activated M2 subtype. Classically activated M1 macrophages rely on glycolysis, whereas alternatively activated M2 macrophages acquire energy from OXPHOS . We found that AOAA seems to switch the metabolism of M1 macrophages towards M2‐like metabolism, as displayed by reduction in lactic acid production and glycolytic rates in conjunction with increment in ATP production.…”
Section: Resultsmentioning
confidence: 75%
“…Blocking glycolysis with 2‐deoxyglucose diminished expression of IL‐4 regulated genes, surface markers and effector functions, and a similar effect was observed when mitochondrial ATP synthesis was inhibited with oligomycin, indicating that glucose can fuel the TCA cycle to support mitochondrial respiration following IL‐4 polarization (Figure ) . However, a recent publication demonstrated that blocking glycolysis via glucose deprivation or galactose supplementation did not affect M(IL‐4) activation, unlike 2‐deoxyglucose treatment . In these settings, IL‐4 activated macrophages could increase the use of alternate pathways, such as glutaminoloysis, to support oxidative metabolism in the absence of glycolytic activity.…”
Section: Alternatively Activated Macrophage Metabolismmentioning
confidence: 99%
“…32,45 However, a recent publication demonstrated that blocking glycolysis via glucose deprivation or galactose supplementation did not affect M(IL-4) activation, unlike 2-deoxyglucose treatment. 46 In these settings, IL-4 activated macrophages could increase the use of alternate pathways, such as glutaminoloysis, to support oxidative metabolism in the absence of glycolytic activity. Furthermore, data suggesting that glucose can fuel fatty acid synthesis to support increased FAO in alternatively activated macrophages provides a link between glycolysis, fatty acid synthesis, and FAO.…”
Section: Alternatively Activated Macrophage Metabolismmentioning
confidence: 99%